Vinte ensaios de adubação N-P-K da cultura do feijão na Zona da Mata, Minas Gerais - Braga, José Mário; Defelipo, Braz Vitor; Vieira, Clibas; A N Fontes, Luiz (Revista Ceres, 2025)
Twenty factorial trials were conducted over a three year period in the Zona da Mata area of Minas lerais to determine the response of dry beans (Phaseolus vulgar s) to applications of ammonium sulfate (N), superphosphate (’) and muriate of potash (K). Zero, 30 and 60 kg/ha of N, zero, 60 and 120 kg/ha of P205 and zero, 40 and 80 kg/ha of N, zero, 60 and 120 kg/ha planting in all possible combinations. From the data obtained.